Role of ICT for Multi-Disciplinary Applications in 2030. - Ligthart, L. P. (River Publishers series in communications., 2016)
The theme of this book is Role of ICT for multi-disciplinary applications in 2030, which is absolutely appropriate to explore with regard to the CONASENSE vision of looking at services utilizing the Communications, Navigation, Sensing and Services (CONASENSE) paradigm in a period of 20-50 years from now. The vision of CONASENSE society is to bring about active integration of the three worlds of communications, navigation and local/remote sensing - that have been apart for years require a multidisciplinary approach. This 4th Communication, Navigation, Sensing and Services (CONASENSE) book brings together in contributions from another society, namely, Global ICT Standardization Forum for India (GISFI).Technical topics discussed in the book include: Wireless Sensor Networks Advanced IoT and M2M Future Space Communications Infrastructure ICT Networks for CONASENSE in 2030 International ICT Research Secure Vehicular Ad-Hoc Networks Heterodox Networks CONASENSE Innovation Era CONASENSE at NanoscaleThus the book provides a rich and interesting coverage of diverse aspects concerning multi-disciplinary applications.